PROTECTION OF CITIZENS' CONSTITUTIONAL RIGHTS THROUGH ADVISORY OPINION AUTHORITY TO THE CONSTITUTIONAL COURT - Bagus, Moh (Gapenas Publisher, 2025)
This article aims to provide new tools to protect the constitutional rights of citizens and strengthen the constitutional democratic guard mechanisms. To strengthen argumentation, it will be parsed systematically based on constitutional authority, advisory opinions to the Court, and limitations on the Court's authority, as mentioned. The method employed by the author is a legal normative approach, utilizing a conceptual, statutory, and comparative framework. Through this approach, the conceptual writer elaborates on the concept of a state of law as a doctrine that encompasses understanding, enforcement, and protection of law in Indonesia. The Constitution of Indonesia and the approach the writer uses to portray the implementation of ex ante abstract review in France and Finland. Research results indicate that it is crucial to safeguard the rights of constitutional citizens and strengthen the mechanisms of a more democratic statecraft. However, this has not yet occurred with existing state authority institutions at present. This involves (1) protecting the rights of constitutional citizens and safeguarding the mechanisms of statehood through preventive efforts. (2) Efforts to prevent can be implemented by giving new authority to the Court Constitution in the form of an advisory opinion. (3). In matters, the connection gives authority. There are apparent limitations in the form of the guard doctrine of the rule of law.